ТАЪЛИМ КЛАСТЕРИ МУҲИТИДА БЎЛАЖАК ЖИСМОНИЙ ТАРБИЯ ЎҚИТУВЧИЛАРИНИНГ КРЕАТИВ КОМПЕТЕНТЛИГИНИ РИВОЖЛАНТИРИШ - Арзиев, Ш. (SCIENCE and SOCIETY, 2022)
This article shows how to develop and use the creative competence of future physical education teachers in an educational cluster. You can obtain materials that will help you to combine the forms and methods of teaching and understand the content of the formed teaching materials.